Saturated distilled monoglycerides variants in gel-form cake emulsifiers - Lee, Lai Yee; Ling, Chin Nyuk; Lim, Chon Hock; Yusof, Yus Aniza; A. Talib, Rosnita (Elsevier, 2014)
Three palm based and one non-palm based saturated distilled monoglycerides (sDMG) were hydrated to form gels and applied into sponge cakes for performances evaluations. The gel structures were similar across the samples. The increase of gel dosage increased cake batter viscosity, aeration, cake specific volume and crumb softness. The performance of sDMG with high monopalmitin and high monostearin gel-form cake emulsifier in sponge cakes were of no significant difference (P > 0.05).